2008
DOI: 10.1152/ajprenal.00401.2007
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways modulated by fish oil in salt-sensitive hypertension

Abstract: Diaz Encarnacion MM, Warner GM, Gray CE, Cheng J, Keryakos HK, Nath KA, Grande JP. Signaling pathways modulated by fish oil in salt-sensitive hypertension. Am J Physiol Renal Physiol 294: F1323-F1335, 2008. First published April 2, 2008 doi:10.1152/ajprenal.00401.2007.-Although many studies have indicated that fish oil (FO) improves cardiovascular risk factors and reduces histopathological manifestations of injury in experimental renal injury models, potential mechanisms underlying this protective effect have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 104 publications
2
13
0
2
Order By: Relevance
“…Furthermore, we suggest that EPA has a blood pressure-lowering effect in our diabetic rats, as it does in several hypertensive models (Din et al, 2004;von Schacky, 2006;Diaz Encarnacion et al, 2008). This may be attributable to improvements in EDHF-and/or EDCF-mediated responses because such responses may contribute to blood pressure homeostasis Vanhoutte, 2004, 2006;Vanhoutte et al, 2005).…”
mentioning
confidence: 78%
“…Furthermore, we suggest that EPA has a blood pressure-lowering effect in our diabetic rats, as it does in several hypertensive models (Din et al, 2004;von Schacky, 2006;Diaz Encarnacion et al, 2008). This may be attributable to improvements in EDHF-and/or EDCF-mediated responses because such responses may contribute to blood pressure homeostasis Vanhoutte, 2004, 2006;Vanhoutte et al, 2005).…”
mentioning
confidence: 78%
“…TNF-␣ and other cytokines stimulate transcription of a number of proinflammatory genes, at least in part through activation of the NF-B signaling pathway (35,42,52). We previously demonstrated that fish oil reduces NF-B activation, inflammation, and renal damage in a salt-sensitive model of hypertension, an effect that is only in part due to reduction in blood pressure (16). A number of in vitro studies implicated activation of ERK, NF-B, and/or AP-1 in the transcriptional regulation of MCP-1 in response to a variety of proinflammatory cytokines (38,43,46,47,52,73,79).…”
mentioning
confidence: 99%
“…In animal studies, DHA reduces systolic blood pressure and vascular wall thickness in spontaneously hypertensive rats25, 62 and aldosterone‐induced hypertension in dogs 27. Our study, however, is the first to elucidate the hypotensive effects of DHA in experimental atherosclerosis induced in mice by feeding a Western diet.…”
Section: Discussionmentioning
confidence: 84%